Impacts of self-confidence cultivation combined with family collaborative nursing on the hope level, stigma and exercise tolerance in patients undergoing radical resection of pulmonary carcinoma - Ye, Fei; Wu, YouHong (Frontiers in Surgery, 2023)
[Abstract] Objective: To analyze the impacts of self-confidence cultivation combined with family members' collaborative nursing on the level of hope, stigma and exercise tolerance in patients with radical operation for lung cancer.Methods: From January 2018 to December 2021, 79 patients who underwent radical operation for lung cancer in our hospital were included and grouped into two groups according to the order of admission. The control group (n=39) received routine care, and the study group (n=40) was given self-confidence training combined with family members' collaborative nursing on the basis of the control group.The level of hope, stigma, exercise tolerance, and cancer-related fatigue were compared. Results: After the intervention, the scores of T, P, I dimensions in Herth Hope Inventory (HHI) and total score in the two groups were higher than those before the intervention (all P<0.05).The scores of T, P, I dimensions and total scores of the HHI in the study group were higher than those in the control group (all P<0.05). After the intervention, the scores of each dimension of the Chinese version of the Chinese version of the Lung Cancer Stigma Scale (CLCSS), the modified British Medical Research Council Dyspnea Scale (mMRC), and the scores of each dimension of the Cancer Fatigue Scale (CFS) were lower than those before the intervention (all P values <0.05),the 6-min walk test (6MWT) result was longer than that before the intervention (both P<0.05),and the scores of each dimension of CLCSS scale, mMRC score, and each dimension of CFS scale in the study group were lower than those in the control group (P<0.05), 6MWT was longer than the control group (P<0.05). Conclusion: Self-confidence cultivation combined with family members' collaborative nursing can promote the level of hope of patients undergoing radical mastectomy for lung cancer, reduce stigma, enhance exercise endurance, and relieve cancer-related fatigue. [Key words] self-confidence cultivation; family members' collaborative nursing; radical operation for lung cancer; hope level; stigma; exercise tolerance